2017
DOI: 10.5222/buchd.2017.157
|View full text |Cite
|
Sign up to set email alerts
|

A case with atypical hand-mouth-foot disease accompanying with onicomadesis and a small-scale outbreak

Abstract: ÖZEl-ayak-ağız hastalığı enterovirüslerden sıklıkla Coxsackievirus A16 ve enterovirüs 71'in neden olduğu bir hastalık olup, toplumda salgınlara yol açabilmektedir. Son zamanlarda klasik el-ayak-ağız hastalığından farklı özellikleri içeren bir atipik form tanımlanmıştır. Bu atipik formda klasik hastalıktan farklı olarak cilt lezyonlarının daha fazla dorsal yüzleri etkilemesi, gövde ve boyunda daha fazla yoğunlaşması, ülse-re ve büllöz formda olması, kabuklanma ile soyulmanın tipik olması ve onikomadezis ile sık… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…There was no rash in any region of the control group. The palms have been reported as the most common site of involvement in the literature (11,15). Ghosh et al reported that 61.10% of 62 patients aged 9 months-20 years were under the age of 12, that 16.10% had a family history of the disease, and that the most common site of involvement was the hand (16).…”
Section: Discussionmentioning
confidence: 99%
“…There was no rash in any region of the control group. The palms have been reported as the most common site of involvement in the literature (11,15). Ghosh et al reported that 61.10% of 62 patients aged 9 months-20 years were under the age of 12, that 16.10% had a family history of the disease, and that the most common site of involvement was the hand (16).…”
Section: Discussionmentioning
confidence: 99%